A comparison of gene expression of Listeria monocytogenes in vitro and in the soft cheese Crescenza. (29th October 2012) - Alessandria, Valentina; Rantsiou, Kalliopi; Dolci, Paola; Zeppa, Giuseppe; Cocolin, Luca
<x xml:space="preserve">Abstract</x> This study focuses on the expression analysis of virulence and stress response genes (plcA, hly, iap and sigB) in 11 different strains of Listeria monocytogenes. The first step of this study considered an in vitro analysis in synthetic laboratory medium. According to statistical analysis, significant differences emerged for genes sigB and plcA. Subsequently, a soft cheese at two temperatures (4 and 12 °C) and for different times (24 and 48 h) was evaluated. Significant expression differences emerged for the condition at 12 °C after 48 h. No association could be observed between gene expression profile and origin of the different strains.